Unravelling binding effects in cyclodextrin inclusion complexes with diamondoid ammonium salt guests. (1st June 2022) - Alešković, Marija; Roca, Sunčica; Jozepović, Ruža; Bregović, Nikola; Šekutor, Marina
Abstract : A hydrophobic tornado – complexation of diamondoid ammonium salts with cyclodextrins in water. Abstract : With an ever-growing application of inclusion complexes of cyclodextrins (CDs) and other hydrophobic guests in pharmaceutical industry and other scientific and industrial fields, the demand for deeper understanding of effects defining their stability increases. In this work we investigated the formation of inclusion complexes of diamondoid derivatives containing the ammonium moiety with β- and γ-cyclodextrins using NMR, ITC and conductometric titrations. The adamantane- and diamantane-based guests containing one ammonium group formed stable 1 : 1 complexes with β-CD, whereas only the diamantane derivative interacted with γ-CD. The thermodynamics of the binding processes was characterized in detail by means of ITC and the origin of the enthalpic and entropic contributions was discussed. Structural features of the complexes were deduced from the data gathered by NOESY NMR and computational studies revealing the key interactions within the inclusion complexes. Surprisingly, the diammonium derivative did not exhibit any affinity towards inclusion in the cavity of the investigated CDs, which was in strong contrast with its behavior when cucurbituril was used as a host. By providing comprehensive structural and thermodynamic data, this study gives a firm basis for understanding the effects defining the stability of inclusion complexes of charged diamondoid guests with cyclodextrins.